Edukasi Risiko Finansial Teknologi pada Pondok Pesantren Rojaul Huda Darun Nasya Kabupaten Bandung Barat - Linna Ismawati; Jatnika Dwi Asri; Kwik Kianggi; Tiara Salsabila (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2021)
Financial Technology is one of the digital-based technological innovations in the era of the industrial revolution 4.0 which massively experienced very rapid growth. The development of financial technology is followed by the community’s ability to adapt financial technology and use it massively in everyday life. Theease of transacting using financial technology applications changes people’s lifestyles from conventional technology to digital technology. On the other hand, limited public knowledge about financial technology has resulted in some people experiencing the risk of loss in the use of digital-based technology. Lack of knowledge raises various problems faced related to financial technology including an increasingly consumptive lifestyle, the risk of online loans that fail to pay, and the risk of investment failure. Based on this, the purpose of this community service and empowerment program is to educate and provide assistance to the students of the Rojaul Huda Darun Nasya Islamic Boarding School in order to have sufficient knowledge in utilizing financial technology and minimizing risk. The methods used are (1) exploring partnerships and discussing service topics (2) carry out observations to find problems that occur with partners; (3) providean explanation of service activities to partners; (4) carry out service activities at partner locations. The output obtained from the implementation of this Service and Empowerment Program is to increase knowledge and soft skills in the use of financial technology by the younger generation. The conclusion of this activity isthe importance of educating the public in the use of financial technology to avoid the risk of loss.